Sleep and Sleep Disorders in Tourette Syndrome: What is Known and What is Still Unknown - Oksenberg, Arie (Current Drug Therapy, 2020)
Background: Most of the patients with Tourette Syndrome (TS) present additional comorbidities. Attention Deficit Hyperactivity Disorder (ADHD) and Obsessive-Compulsive Disorder (OCD) are the most common. Sleep Disorder has been suggested also as common comorbidity. Objective: To review the literature on sleep characteristics and sleep disorder in patients with Tourette Syndrome (TS), with emphasis on the contribution of specific co-morbidities to the severity of impaired sleep and life quality of the patients. Results: In general, sleep problems are not frequent at the age when tics appear which are estimated to affect about 10 % of these children. In severe cases, tics appear in all sleep stages. In a large study, the prevalence of sleep problems was 17.8% but was 12 % in “TS-only” (9.4% in children and 7.5 in adults) compared to 22% in children and 18% in adults with TS+ADHD. Unfortunately, in most of the studies, the characteristics of these “sleep problems” are not defined. In spite of the scarcity of data, the two main sleep disorders in TS patients are insomnia and parasomnias. Although much more data is needed, many TS subjects are sleep deprived (which exacerbate the tics) and may suffer from excessive daytime sleepiness, which negatively affects normal functioning. Conclusions: Although the literature is not conclusive, children and adolescents with TS appear to suffer more from sleep disturbances and sleep disorders than age-matched controls. Not all patients have tics during sleep, but in severe cases, tics may appear in all sleep stages. It is clear that when patients present both TS and ADHD, (a very common condition), the sleep difficulties are related mainly to ADHD. Much more research is warranted in all aspects of sleep and sleep disorders in TS.
Keywords: tics